A multi-platform approach to promote clinical and research activities in nutrition and pediatric oncology - Amita Trehan; Elena J. Ladas (Elsevier, 2020)
The increased risk of mortality and treatment-related toxicities among children with cancer who are also malnourished has prompted several efforts aimed at improving access to clinical care and promoting high-quality research in nutrition and pediatric oncology. The presence of strong nutrition programs in pediatric cancer units located in low- and middle-income countries where endemic rates of malnutrition, nutrient deficiencies and food insecurity are high makes this an even more crucial component of pediatric cancer care. This is especially true in Southeast Asia where nearly 30% of children in the region experience severe acute malnutrition at some point in childhood. Several global initiatives have been put forth to support pediatric cancer units in closing this disparity in nutritional care by increasing the availability of nutritionists knowledgeable in the provision of nutrition care to children with cancer. This report provides highlights of several collaborative, global initiatives aimed at further improving the quality of care, increasing education opportunities, and fostering multi-disciplinary collaborations in nutrition and research in pediatric oncology. Keywords: Pediatric oncology, Childhood cancer, Nutrition, Supportive care